PENGARUH REMEDIAL TERHADAP HASIL BELAJAR EKONOMI SISWA DI SMA NEGERI 1 RANTO BAEK KABUPATEN MANDAILING NATAL T.A 2021/2022 - Nurhasti Nurhasti; Rijal Rijal (Jurnal Inovasi Penelitian, 2022)
The type of research used is quantitative research. The instrument used in this study is in the form of questions based on a questionnaire that has been prepared with a total of 20 statements. From the research results obtained constant values ​​a = 1.02 and b = -0.23. Thus the equation of a simple linear line is Y = 1.02+-0.23X. In this case b is positive, it can be concluded that student learning outcomes (variable Y) increased by -0.23. While the results of hypothesis testing indicate that the value of t_(count ) is 0.34 while the magnitude of t_(table ) at a significant level of 5% with dk = n-2 = 42-2 = 40 is 1.68. Because t_hitung t_table or 0.34 1.68 then the formulation of the hypothesis that has been set in this study can be accepted as true. Thus, it can be concluded that there is a positive and significant effect of remedial on student learning outcomes in economics learning in class X IIS SMA Negeri 1 Ranto Baek, Mandailing Natal Regency T.A 2021/2022.